Discriminant effect of morphology and range of attack on the performance level of volleyball players - Araujo Tinoco Cabral, B. G.; de Araujo Tinoco Cabral, S.; Ferreira de Miranda, H.; Moreira Silva Dantas, P.; Machado Reis, V. (Revista Brasileira de Cineantropometria e Desempenho Humano, 2011)
The aim of this study was to identify the discriminant effect of morphology and range of attack-related variables on the performance level of under-17 female volleyball players. The sample consisted of young volleyball players (n=40) divided into two groups: players of the Brazilian national team (n=21) aged 15.86 ± 0.36 years, body weight of 68.11 ± 8.73 kg, and height of 181.61 ± 6.11 cm, and players of the state team of Rio Grande do Norte (n=19) aged 15.16 ± 0.88 years, body weight of 60.54 ± 7.60 kg, and height of 170.52 ± 7.97 cm. The somatotype was assessed using the Heath & Carter method. A modified Sargent test was used to assess vertical jump height and maximum attack height. The measures were compared between the two groups using the Student t-test for independent samples. Discriminant function analysis was applied to predict group allocation using the measures obtained as independent variables. The two groups differed significantly in terms of body weight, fat mass, height, maximum attack height, range of attack, and somatotype. Discriminant function analysis identified the somato-type measures (endomorphy, ectomorphy, and mesomorphy) with correlation coefficients below 0.30. The canonical correlation coefficient obtained with this function was 0.856. In conclusion, somatotype or vertical jump ability does not seem to distinguish elite athletes from non-elite athletes in under-17 female volleyball players, and height is the main morphological determinant to achieve elite level performance.